Effect of oil palm planting materials, rainfall, number of male inflorescence and spikelet on the population abundance of oil palm pollinator, Elaeidobius Kamerunicus faust (Coleoptera: Curculionidae) - Nurul Fatihah Abd Latip,; Mohd Rizuan Zainal Abidin,; Idris Abd Ghani,; Muhamad Fahmi M. H.,; Luqman H. A.,; H Al – Talafha,; Noor Nasuha A.A., (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
Elaeidobius kamerunicus is the main insect pollinator of oil palm and was first introduced to Malaysia in the year of 1980s. This introduction had increased the oil palm yield production. However, the yield production has obviously declined lately. There are several factors that contributing to the declined and most said is because of the E. kamerunicus population itself. As such, a study to determine the population abundance of E. kamerunicus on different oil palm planting materials was done at Ladang FELDA in Jengka, Pahang, Malaysia from May 2016 to April 2017. A total of nine spikelets, three each from top, middle and bottom section of male inflorescence which were systematically selected prior to data collection, were cut off early in the morning and brought back to Centre for Insect Systematics, UKM for E. kamerunicus counts. The mean population abundance of E. kamerunicus per ha for both oil palm clones and D×P were 20463 ± 3528 and 11079 ± 2135 weevils per ha, respectively. Based on previous studies in Malaysia and elsewhere, the E. kamerunicus populations in this plantation are adequate to pollinate the female inflorescence. Oil palm clones has higher number of spikelet due to uniformity of the plantlets and the number of male inflorescence showed positively correlated with the population abundance of E. kamerunicus per ha, suggesting that these factors were favorable for E. kamerunicus activities. However, further study is needed to determine the relationship between E. kamerunicus population on different oil palm planting materials and the fruit set.